Different Flour Microbial Communities Drive to Sourdoughs Characterized by Diverse Bacterial Strains and Free Amino Acid Profiles - Celano, Giuseppe; De Angelis, Maria; Minervini, Fabio; Gobbetti, Marco (Frontiers in Microbiology, 2016)
This work aimed to investigate whether different microbial assemblies in flour may influence the microbiological and biochemical characteristics of traditional sourdough. To reach this purpose, members of lactic acid bacteria, enterobacteria, and yeasts were isolated from durum wheat flour. Secondly, the isolated microorganisms (Pediococcus pentosaceus, Saccharomyces cerevisiae, Pantoea agglomerans, and Escherichia hermanni) were inoculated in doughs prepared with irradiated flour (gamma rays at 10 kGy), so that eight different microbial assemblies were obtained. Two non-inoculated controls were prepared, one of which (C-IF) using irradiated flour and the other (C) using non-irradiated flour. As shown by plate counts, irradiation of flour caused total inactivation of yeasts and a decrease of all the other microbial populations. However acidification occurred also in the dough C-IF, due to metabolic activity of P. pentosaceus that had survived irradiation. After six fermentations, P. pentosaceus was the dominant lactic acid bacterium species in all the sourdoughs produced with irradiated flour (IF). Yet, IF-based sourdoughs broadly differed from each other in terms of strains of P. pentosaceus, probably due to the different microorganisms initially inoculated. Quantitative and qualitative differences of free amino acids concentration were found among the sourdoughs, possibly because of different microbial communities. In addition, as shown by culture-independent analysis (16S metagenetics), irradiation of flour lowered and modified microbial diversity of sourdough ecosystem.